Epidemiological and Bacteriological Profile of Urinary Tract Infection and the Antibiotic Sensitivity Pattern of Causative Organisms in National Medical College and Teaching Hospital - A Retrospective Cross-Sectional Study (Med Phoenix, 2020)
Background: Urinary tract infections (UTIs) are one of the most common infectious conditions seeking treatment. There are varieties of microorganisms associated. The bacteriological investigations are incomplete without antibiotic sensitivity test of the isolate. Our aim is to determine age and sex distribution of UTI, bacteriological profile, and antibiotic sensitivity pattern of the organisms.Materials and Methods: A retrospective cross-sectional observational study of records of patients with clinically suspected UTI from Kartik 2076 to Magh 2076 was conducted at National Medical College and Teaching Hospital (NMCTH). It included both inpatient and OPD visit patients who submitted their clean-catch midstream urine sample for culture and antibiotic sensitivity at Microbiology lab of NMCTH.Result: Out of 385 patients, 103 (26.75%) showed bacterial growth. Escherichia coli (47.58 %) was the most common organism followed by Staphylococcus sps. (18.45%) and Klebsiella sps.(17.47%) respectively. There was female dominance (62.13%) but male were predominantly affected in children and older population. The most common age group for UTI was 21-30 years (mean age 25 years) and females were more affected than males. The most common pathogen was Escherichia coli, followed by Staphylococcal sps. and Klebsiella. All the organisms showed best sensitivity to tigecycline (100%).Conclusion: This study highlights the common pathogens causing UTI and their antibiotic sensitivity patterns which could help clinicians in starting rational empirical antibiotic therapy for such patients while awaiting urine culture reports.